Jogos tradicionais e percepção ecológica das cores nas aulas de educação física - Araújo, Kelly Cristina Alves de (2018)
This is a participatory type of research, with an analytical approach to the data that presents the results of the Program of Sensory Games for Early Childhood Education (PROJSEI), with a focus on visual perception, with thirty children aged four and five years old, from students of elementary school of the Federal University of Paraíba. The goal was to analyze the influence of colors in the change of the perception. The PROJSEI Sensory Games was taught in twelve lessons for each class, each course lasting one hour in a total period of two months. The intervention proposal in the school fulfilled the following steps: a) "Presentation", in which the research project was presented to the pedagogical coordination and to the teachers of the classes, so that they could have access to the class schedule and the documentation; b) "Evaluation", at this stage, the children were observed in the movement situations, which games they played, what spaces of the school they used the most, having as a subsidy for this process a roadmap of observation; c) "Conversation", we elaborated a semi-structured interview script in which, from a walk through the school premises, with the aid of a portable camcorder for the proper registration, we were interviewing the children with the purpose of knowing their routine in the school; d) "Realization", in which the actual classes were carried out, seeking to integrate all the students, based on the laboratory-class structured of the Corpodeity Pedagogy which is a pedagogical proposal for physical education, in which the game is understood as a movement situation with possibility to the experience of playing in artistic, educative and therapeutic dimensions aiming to encourage the existential rewriting for a more creative way of life. In order to more accurately evaluate the results of PROJSEI sensory games, the observation script served as an instrument to separate the classes into three phases: recognition, intervention I and intervention II, better organizing the units context in the phases and developing the possibilities presented in the registration units; the classes took place twice a week, two classes were distributed for the recognition phase, five classes for the intervention phase I and five classes for the intervention phase II. To analyze the data, we used content analysis and discussion based on Gibsonian ecological theory. The results of the intervention and analysis of the data are presented in article 1 "Perception-action in Physical Education classes: an analysis from the movements of children in games" in which we analyze, in applied games, the possibilities of movement in the game, as well as the possibilities that arose between the agent (child) and the environment (school) constituting affordances, and in article 2 "The movements created through the ecological perception of colors in physical education classes", realizing how the students explored the environment using the available objects and colors in space to facilitate and create new actions in class.